Understanding of Ulama (Religious Scholars) In The Salafi Methodology In Determining The Criteria For Spouse (Case Study In The City of Banjarmasin) - Zaid Ismail, Muhammad; Nadiyah, Nadiyah (JOURNAL OF ISLAMIC AND LAW STUDIES, 2023)
Abstract: The abundance of religious traditions in Banjarmasin often becomes a topic of controversy among the community. Some claim that these traditions are considered bid'ah or innovations in religion, lacking evidence or examples from the Prophet Muhammad (peace be upon him), his companions, the Tabi'in, and the Tabi'ut Tabi'in. This research aims to understand how scholars following the Salafi methodology determine the criteria for choosing a spouse, the legal evidence supporting their understanding, and the standards of compatibility (kafa'ah) in marriage. The study is beneficial for recognizing changes in the phenomenon related to the determination of spouse criteria among the community. This empirical legal research focuses on Salafi scholars in the city of Banjarmasin as research subjects, utilizing interview methods to gather data on the scholars' understanding of determining spouse criteria. The findings of this research indicate that the understanding among the four informants is relatively similar, emphasizing the selection of a partner with a strong religious foundation, good character, and a shared Salafi methodology. Keyword: Manhaj Salaf;Salafi;Spouse. Abstrak: Banyaknya tradisi keagamaan di Banjarmasin sering menjadi polemik dikalangan masyarakat. Ada yang mengatakan tradisi-tradisi yang ada merupakan perbuatan bid’ah atau suatu perkara baru dalam agama yang tidak ada dalil atau contoh dari Rasulullah Shallallahu ‘alaihi wa sallam. maupun para sahabat, tabi’in, dan tabi’ut tabi’in. Penelitian ini bertujuan untuk mengetahui bagaimana pemahaman ulama manhaj salaf dalam penentuan kriteria pasangan hidup, dalil hukum dalam memberikan pemahaman, dan terkait standar ukuran kafa’ah dalam pernikahan. Penelitian ini bermanfaat untuk mengetahui adanya perubahan fenomena dikalangan masyarakat terkait penentuan kriteria pasangan hidup. Jenis penelitian ini adalah penelitian hukum empiris yang menjadikan ulama manhaj salaf di Kota Banjarmasin sebagai subjek penelitian dengan menggunakan metode wawancara yang menghasilkan data berupa pemahaman ulama manhaj salaf dalam penentuan kriteria pasangan hidup. Hasil penelitian ini menunjukkan bahwa pemahaman empat informan relarif sama, yaitu menganjurkan untuk memilih pasangan yang mempunyai agama, akhlak yang baik dan memiliki paham keagamaan yang sama yaitu sama-sama bermanhaj salaf.